Essays in Russian and Soviet History : in Honor of Geroid Tanquary Robinson - Curtiss, John Shelton (Leiden : E.J. Brill, 1965)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: politieke geschiedenis; Rusland; Sovjet-Unie.